Social Accountability Between Consensus and Confrontation: Developing a Theoretical Framework for Societal Accountability Relationships of Public Sector Organizations. Issue 7 (August 2021) - Brummel, Lars
Numerous politicians and scholars have argued that accountability of public authorities to citizens, clients, and societal actors is needed in the current age of governance. Academic debates about social accountability are however scattered with incompatible conceptualizations, high normative expectations, and sobering findings. This article develops an in-depth framework that provides a comprehensive definition and typology of social accountability. It discusses major empirical challenges to social accountability and multiple behavioral styles within social accountability. By distinguishing consensual and confrontational styles of account-holding and account-giving, this article shows that social accountability could serve multiple purposes that go beyond rosy ideals.